RESTORATIVE JUSTICE TERHADAP PELAKU TINDAK PIDANA PENGANIAYAAN (STUDI PUTUSAN NO. 63/PID.B/2021/PN.SKM): Restorative Justice Towards The Prepetrator Of Persecution (Study Of Decision No. 63/Pid.B/2021/Pn.Skm) - Utami, Putri Rizki; Multiwijaya, Vientje Ratna (AMICUS CURIAE, 2024)
Restorative Justice is an effort to resolve criminal acts by bringing together both parties to find a fair solution. The use of Restorative Justice by the judge against the perpetrators of the criminal act of persecution in this case is not appropriate, because peace has been made outside the court and there is no determination of the judge in advance. The subject matter raised based on Decision Number 63/Pid.B/2021/PN. Skm is whether restorative justice against perpetrators of criminal acts of persecution based on Article 351 paragraph (1) of the Criminal Code is considered appropriate or not? (Decision No. 63/Pid.B/2021/PN. Skm) and; Are criminal sanctions in the form of release from lawsuits in accordance with the purpose of prosecution? (Decision No. 63/Pid.B/2021/PN. Skm). This study used a normative research method known as descriptive analysis, which relied on secondary data collected through literature review and analyzed qualitatively to reach the following conclusions: (1) Restorative Justice shall not be applied to those responsible for the crime of persecution under Article 351 paragraph (1) of the Criminal Code. (2) Criminal sanctions in the form of release from lawsuits are not in accordance with the purpose of prosecution. The results of the study associated with the implementation of restorative justice stated that there must be an out-of-court determination first and based on the purpose of 3R + 1D prosecution, the defendant should be a subject to prosecution based on Article 351 paragraph (1) concerning persecution.